Impacts of the Southeast Asian Financial Crisis on the Philippine Manufacturing Sector - Mario B. Lamberte; Aniceto Jr. C. Orbeta; Caesar B. Cororaton; Margarita F. Guerrero (Philippine Institute for Development Studies (PIDS), 1999)
This study examines the impacts of the Southeast Asian financial crisis that struck in July 1997 on the Philippine industries and their responses to such crisis using firm level data from a sample of 541 manufacturing establishments. The survey results clearly show that the capacity utilization rate of the Philippine manufacturing firms started to decline even before the crisis struck in July 1997, and that it continued to drop as the crisis deepened. Thus, the current capacity underutilization rate may be attributed to both cyclical and structural factors. The results of this study do not provide a clear evidence on the existence of a supply-side credit crunch during the crisis period. The significant drop in capacity utilization rate and output of firms during the crisis period would have required a large labor lay-off. However, to minimize the laying off of labor, firms resorted to other means, such as reducing workweek or days, applying forced vacation leave and freezing salary increases, to save some jobs. The study recommends that the government institute some measures to stimulate aggregate demand for 1999. Both monetary and fiscal policies are required to support such expansionary policy.
Keywords: 330; Asian financial crisis; manufacturing sector